PULMONARY PARAGONIMIASIS IN A PATIENT WITH INTRACEREBRAL HEMORRHAGE: A CASE REPORT FROM HANOI MEDICAL UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
This report describes a clinical case of a patient admitted with intracerebral hemorrhage secondary to hypertension, with a significant 10-year history of chronic hemoptysis. The patient had been repeatedly misdiagnosed with chronic bronchitis or pneumonia at multiple healthcare facilities. During hospitalization, the clinical course became exceptionally complex, involving a series of medical complications. A definitive diagnosis of pulmonary paragonimiasis was established on the 7th day of admission following the recovery of Paragonimus eggs from both endotracheal aspirates and stool samples, complemented by a positive ELISA serology. Radiological findings from chest X-ray and CT scans revealed characteristic lesions of paragonimiasis, which were managed with a specific regimen of praziquantel in conjunction with intensive supportive care. After more than one month of treatment, parasitological clearance was achieved, and the patient was stabilized and subsequently discharged. This case study aims to provide valuable clinical insights into the diagnostic considerations, therapeutic strategies, and prognostic implications of paragonimiasis, particularly in patients presenting with chronic hemoptysis where complex underlying comorbidities may mask parasitic symptoms.
Keywords: Paragonimiasis, intracerebral hemorrhage, Tuyen Quang.